THE ANTIULCER ACTIVITY OF THE ROOT EXTRACTS OF TULBAGHIA VIOLACEA - Ntobaki, L.; Makhanya, N.; Opoku, A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
A peptic ulcer is the erosion of a circumscribed area of tissue in the wall of the gastrointestinal tract that is accessible to gastric secretions. Although the initiating cause of ulcers is not clear, Helicobacter pylori, free radicals, inflammation, excessive stomach acid and pepsin emerge as likely factors. The antiulcer activity of Tulbaghia violacea (used by Zulu traditional healers in treating and managing peptic ulcers and other stomach ailments) was investigated. Methanolic extracts (5mg/100ml) of the plant showed little free radical scavenging activity against DPPH (29%) and ABTS (20%) and exhibited a low reducing power. However, the extract significantly inhibited the activities of lipooxygenase, xanthine oxidase, and other lipid peroxidative reactions. Plant extracts exhibited antimicrobial activities against Staphylococcus aureas, Proteus mirabilis (MIC value < 1.0 mg/ml); Streptococcus faecalis, Enterobacter cloacae, Escherichia coli, Proteas vulgaris, and Helicobacter pylori (MIC value = 2.0 mg/ml). The extract was able to protect (p< 0.01) the stomach lining against indomethacin-induced ulceration. We conclude that Tulbaghia violacea root extract has little hydrogen atom donor potential and may not break free radical chain reactions but could act as an anti acid. Its potential in the inhibition of free radical generation, along with its antimicrobial activity justify its use by traditional healers for the treatment of peptic ulcers.